Edukasi EDUKASI VIDEO PRODUK PANGAN KACANG GUDE BAGI GURU KABUPATEN BURU SELATAN - Alwi Smith; Kristin Sangur; Ferymon Mahulette; Ritha Lusian Karuwal (German für Gesellschaft (J-Gefüge), 2023)
Currently public education can be done through the use of video. This is done so that activities run smoothly and save time, as well as benefit people who are not familiar with the potential of pigeon pea. Pigeon pea as a functional plant for the Kisar people can be processed into functional food products such as sweet soy sauce, jam, sweetened condensed milk, pigeon pea extract, gude crackers, and cajanus bar. For this reason, this video is very important to do to explain the tools and materials that need to be prepared and how to make these food products to Science/Biology and Craft teachers. This educational activity method is carried out through preparation and implementation activities for one month. The results obtained are that science/biology and craft teachers can get to know pigeon pea, understand tools and materials and how to make functional food products. Recommendations for this educational activity can be implemented in the curriculum for crafts at the junior and senior high school levels